BELIEF SYSTEM SISWA DALAM PEMBELAJARAN BAHASA INDONESIA DI SMA NEGERI 1 KOTA SOLOK - Mega Putri; Syahrul Ramadhan; Yuli Triarina (JURNAL KONFIKS, 2026)
This study aims to describe the forms of students’ belief systems in Indonesian language learning at SMA Negeri 1 Kota Solok and to explain students’ engagement in language-learning activities. This study employed a qualitative approach with a case study design. Data were collected through classroom observations, in-depth interviews, and documentation, and were analyzed through data reduction, data display, and conclusion drawing. Data trustworthiness was ensured through source and technique triangulation. The findings reveal that students’ belief systems are reflected in three main dimensions: belief in language ability (self-efficacy), belief in the learning process, and belief in teachers and the learning environment. Most students demonstrated positive belief systems, as reflected in their confidence in understanding texts, writing, expressing opinions, and participating in classroom activities. The findings also indicate that belief systems contribute to students’ engagement in reading, writing, speaking, and listening activities. Supportive learning environments, constructive teacher feedback, and a strong school literacy culture further strengthened students’ beliefs and participation in Indonesian language learning.